Sensitivity Analysis of the Dynamical Spread of Ebola Virus Disease - Akanni, J. O.; Akinpelu, F.O; Oladejo, J. K.; Opaleye, S. E. (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2017)
The deterministic epidemiological model of (S, E, Iu, Id, R) were studied to gain insight into the dynamical spread of Ebola virus disease. Local and global stability of the model are explored for disease-free and endemic equilibria. Sensitivity analysis is performed on basic reproduction number to check the importance of each parameter on the transmission of Ebola disease. Positivity solution is analyzed for mathematical and epidemiological posedness of the model. Numerical simulation was analyzed by MAPLE 18 software using embedded Runge-Kutta method of order (4) which shows the parameter that has high impact in the spread of the disease spread of Ebola virus disease.